Effectiveness of Active Cycle of Breathing Technique on Peak Expiratory Flow Following Cardiac Surgery - Susy Puspasari; Nyayu Nina Putri Calisanie; Nunung Nurhayati; Septa Permana; Indriyani Lestari (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Introduction: Pulmonary dysfunction is a common complication following cardiac surgery, resulting from reduced lung expansion, postoperative pain, secretion retention, and impaired ventilation. These complications may delay recovery and increase the risk of pulmonary morbidity. The Active Cycle of Breathing Technique (ACBT) has been recommended as a pulmonary rehabilitation strategy to improve airway clearance and restore lung function; however, evidence regarding its effectiveness in Indonesian postoperative cardiac patients remains limited. Objective: To evaluate the effectiveness of the Active Cycle of Breathing Technique (ACBT) in improving peak expiratory flow (PEF) among patients after cardiac surgery. Methods: A quasi-experimental study with a one-group pretest–posttest design was conducted among 114 adult patients who underwent cardiac surgery at the General Intensive Care Unit of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Participants were recruited using accidental sampling. ACBT was administered for four consecutive postoperative days. Peak expiratory flow was measured using a peak flow meter before the intervention on postoperative day 1 and after completion of the intervention on postoperative day 4. Data were analyzed using descriptive statistics and paired t-test. Results: The mean peak expiratory flow increased significantly from 228.30 ± 32.6 L/min before the intervention to 442.32 ± 43.7 L/min after four days of ACBT. Paired t-test analysis demonstrated a statistically significant improvement in PEF following the intervention (p < 0.001). A strong positive correlation was observed between pretest and posttest measurements (r = 0.786, p = 0.001). Conclusion: ACBT significantly improved peak expiratory flow in patients after cardiac surgery. Incorporating ACBT into routine postoperative pulmonary rehabilitation may facilitate recovery of lung function and support early postoperative respiratory management.